Pengaruh model pembelajaran kooperatif TGT terhadap hasil belajar IPA ditinjau dari kemampuan kerja sama - Eka Indriyani Safarina (Universitas Sarjanawiyata Tamansiswa, 2018)
This study descriptively aims to identify the result of the learning of science which was used the cooperative learning model Teams Games Tournament (TGT) and conventional model viewed from ability of teamwork on the students in eight grade of SMP Negeri 4 Wonosari in academic year 2016/2017. Comperitavely to determine the difference of the science learning result between the cooperative learning model Teams Games Tournament (TGT) and conventional model viewed from ability of teamwork on the student in eight grade of SMP Negeri 4 Wonosari in academic year 2016/2017. This study belongs to quasi experiment. The result of this study descriptively showed that the tendency of the learning result used the cooperative learning model Teams Games Tournament (TGT) was the highest category and the learning result which was used conventional model belongs to the medium category. The identify of teamwork abiltiy reviewed used cooperative learning model Teams Games Tournament (TGT) was the high category and conventional model was the medium category. Comperatively there was a significance difference of the science learning result between the learning used the cooperative learning model Teams Games Tournament (TGT) and conventional model viewed from ability of teamwork on the student in eight grade of SMP Negeri 4 Wonosari in academic year 2016/2017. The average of the learning result that the cooperative learning model Teams Games Tournament (TGT) was higher conventional model, it means that there was the influence of cooperative learning model Teams Games Tournament (TGT) type to the learning result of science viewed from ability of teamwork student grade VIII SMP Negeri 4 Wonosari academic year 2016/2017.